2023
DOI: 10.1146/annurev-earth-032320-104209
|View full text |Cite
|
Sign up to set email alerts
|

The Mid-Pleistocene Climate Transition

Abstract: The timing of ice ages over the past ∼2,600 thousand years (kyr) follows pacing by cyclical changes in three aspects of Earth's orbit that influence the solar energy received as a function of latitude and season. Explaining the large magnitude of the climate changes is challenging, particularly so across the period of time from ∼1,250 to 750 ka—the Mid-Pleistocene Transition or MPT. The average repeat time of ice age cycles changed from an earlier 41-kyr rhythm to longer and more intense glaciations at a spaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 158 publications
(304 reference statements)
0
1
0
Order By: Relevance
“…This interval belongs to the later part of the MPT, characterized by extended glacial conditions (Fig. 5c) (Clark et al, 2006;Bol'Shakov, 2015;Daruka and Ditlevsen, 2016;Herbert, 2023). This period signifies a sudden reorganization of the climate system, occurring in at least two discernible stages, i.e., MIS 25-22 and MIS 22-16.…”
Section: Relative Variation Of 10 Bereac and 9 Bereacmentioning
confidence: 99%
“…This interval belongs to the later part of the MPT, characterized by extended glacial conditions (Fig. 5c) (Clark et al, 2006;Bol'Shakov, 2015;Daruka and Ditlevsen, 2016;Herbert, 2023). This period signifies a sudden reorganization of the climate system, occurring in at least two discernible stages, i.e., MIS 25-22 and MIS 22-16.…”
Section: Relative Variation Of 10 Bereac and 9 Bereacmentioning
confidence: 99%
“…There is, in fact, little support for such a scenario. Overall, Earth has had the same climate regime during the last ~1 million years, since the shift to deep, long (~100 kyr) glacial-interglacial cycles with the Mid-Pleistocene Climate Transition (Clark et al, 2006;Herbert, 2023). Maximal Pleistocene ice sheet cover in the Northern Hemisphere was attained during multiple Middle Pleistocene glaciations rather than during the last glacial cycle (Batchelor et al, 2019).…”
Section: Climatic Causationmentioning
confidence: 99%
“…This period in the Benguela region was characterized by higher SST variations linked to 41-kyr obliquity cycles as well as the increase of the meridional thermal gradient, which led to the intensification of the upwelling phases (Christensen and Giraudeau, 2002;Etourneau et al, 2009;Martinez-Garcia et al, 2010;Rosell-Melé et al, 2014) and the alternation of possible Benguela Niño/Niña conditions. The highest amplitude of SST glacial-interglacial variability was recorded during the Early-Middle Pleistocene Transition (EMPT), a period between 1.4 and 0.4 Ma, during which a switch from 41-kyr to 100-kyr orbital cycle occurred (Berger and Jansen, 1994;Head and Gibbard, 2015;Herbert, 2023). The planktonic foraminiferal dataset for Hole U1575A and U1576A detected phases of southward/northward shifts of the ABF (up to 24°35´ S), within part of the studied stratigraphic sequence corresponding to the EMPT (Fig.…”
Section: Variations Of the Paleoceanographic Conditions During The Qu...mentioning
confidence: 99%
“…Several studies suggested the occurrence of Benguela Niño/Niña events during the Pliocene-Pleistocene time intervals (e.g., Ufkes and Kroon, 2012;Rosell-Melé et al, 2014). Particularly, since the onset of the Early-Middle Pleistocene Transition (EMPT), a strong glacial-interglacial sea surface temperature (SST) variability occurred, possibly promoting the development of Benguela Niño/Niña conditions (Herbert, 2023).…”
mentioning
confidence: 99%